The Legacy of the Nineteenth Amendment Centennial - Allison K. Lange (Transatlantica)
The Nineteenth Amendment centennial in 2020 prompted significant historical research and a wave of public-oriented projects. These works altered the long familiar narrative of the history of women’s voting rights that featured white female leaders, their organizations, and the turning points that they established in their early histories of the movement. Although the pandemic changed plans, the centennial commemorations resulted in an updated history, a wealth of new resources, and a vital scholarly community.